A pluralist theory of constitutional justice : assessing liberal democracy in times of rising populism and illiberalism - Rosenfeld, Michel, 1948- (Oxford : Oxford University Press, 2022)
This resource provides a systematic account of the role of distributive justice in the normative legitimation of liberal constitutions. The requirements of distributive justice are highly contested, and constitutions are susceptible to influencing those they govern. Rosenfeld suggests that liberal constitutions must incorporate 'justice essentials'.
Also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 23, 2022).
Keywords: Liberalism; Justice; Constitutional law; Politics and Government; Politics & government